El relato proléptico en la épica: Fineo como narrador interno en Argonáuticas de Apolonio de Rodas (Argos, 2025)
One type of prolepsis, frequently used in the Argonautica, is theprogrammatic speech in which a character anticipates the subsequentstory. In this manner works the story of Phineus as navigation guidance forthe Argonauts. With the inevitable model of travel stories of Odyssey, thisinternal narrative keeps a mirror-relationship with the work that containsit and carries a quasi-identification between internal narrator and mainnarrator. This article aims to analyze the narrative levels in this story, toshow how this anticipatory technique works in the poem on a metaliterarylevel.